Pengaruh Akuntansi Hijau dan Kinerja Lingkungan terhadap Kinerja Keuangan pada Perusahaan Sektor Kimia yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Fannya Mutiara Sari; Annisa Ari Suci; Mufita Dea Ananta; Maria Yovita R. Pandin (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to examine the influence of green accounting and environmental performance on financial performance in chemical sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. The independent variables used are green accounting (X1), measured using environmental costs, and environmental performance (X2), measured using the PROPER rating, while the dependent variable is financial performance measured by ROE. The sample consists of 20 companies selected through purposive sampling, and data analysis is conducted using multiple linear regression with SPSS. The t-test results show that green accounting has a significant negative effect on financial performance, while environmental performance has a significant positive effect. The F-test indicates that both independent variables together have a significant positive effect on financial performance.